Building learning cultures in the child welfare workforce. (April 2019) - Julien-Chinn, Francie J.; Lietz, Cynthia A.
Abstract: Creating organizational change, including implementing evidence based practices, requires agencies to have supportive learning cultures. Despite ongoing efforts to implement best practice, translation of practice principles to child welfare practice is inconsistent; some research suggests this is in part due to organizational barriers. According to Organizational Theory, organizations are governed by their culture and climate. If agencies seek to advance evidence based practices, creating a learning culture is one way to form a supportive context for this work. This study explored the relationship of supervisory processes such as reflective supervision and group supervision to the degree to which staff observed a learning culture. Findings suggest workers who report high levels of reflective supervision and those who participated in group supervision, reported experiencing a higher level of learning culture. Findings offer implications for ways organizations can adapt supervisory procedures to create a culture that is theoretically consistent with best practices.